Hydrothermal synthesis of 3D Ba5Ta4O15 flower-like microsphere photocatalyst with high photocatalytic properties. Issue 17 (19th August 2016) - Xu, Dongbo; Shi, Weidong; Xu, Chao; Yang, Songbo; Bai, Hongye; Song, Chengjie; Chen, Biyi
Abstract: Abstract : A novel and efficient photocatalyst of three dimensional (3D) Ba5 Ta4 O15 flower-like microsphere was synthesized via an alkaline etch under hydrothermal condition. The influence of reaction temperature, reaction time, and alkaline concentration on the morphology were investigated for the 3D Ba5 Ta4 O15 flower-like microsphere photocatalyst. The morphology and structure of the 3D Ba5 Ta4 O15 were characterized using x-ray diffraction, scanning electron microscope, transmission electron microscope, and high-resolution transmission electron microscopy. The results show that the elegant flower-like structure was composed of Ba5 Ta4 O15 nanosheets. The 3D Ba5 Ta4 O15 flower-like microspheres show a higher photocatalytic activity in the degradation of methylene blue under ultraviolet light than the bulk Ba5 Ta4 O15 microcrystal by the solid-state-reacted synthesized. The UV–vis diffuse reflectance spectra, photoluminescence spectra, volumetric adsorption method, and photocurrent response of the Ba5 Ta4 O15 photocatalyst were characterized indicated that the higher photocatalytic activity of flower-like Ba5 Ta4 O15 microspheres was due to the high crystallinity, large surface area and the effective charge separation.